Protocol to measure ribosome density along mRNA transcripts of Arabidopsis thaliana tissues using Ribo-seq - Isabel Cristina Vélez-Bermúdez; Shu-Jen Chou; Ai-Ping Chen; Wen-Dar Lin; Wolfgang Schmidt (STAR Protocols, 2023)
Summary: Ribosome profiling (Ribo-seq) measures ribosome density along messenger RNA (mRNA) transcripts and is used to estimate the “translational fitness” of a given mRNA in response to environmental or developmental cues with high resolution. Here, we describe a protocol for Ribo-seq in plants adapted for the model plant Arabidopsis thaliana. We describe steps for lysis and nucleolytic digestion and ribosome footprinting. We then detail library construction, sequencing, and data analysis. : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.